Clinical trials on oncolytic viruses - I. V. Golovinov; A. S. Goncharova; A. A. Shulga; S. N. Vlasov; S. N. Dimitriadi (Бюллетень сибирской медицины)
Oncolytic viruses (OVs) are a new class of targeted anticancer drugs with unique mechanisms of action. Oncolytic virotherapy has evolved from the use of in vitro-passaged strains (first generation) to genetically engineered viruses with increased selectivity (second generation) and, ultimately, to recombinant OVs expressing a transgene (third generation).The aim of the review was to analyze and summarize data on the current state of clinical research on OVs.A PubMed search identified 182 articles from 1997 to 2024 with 154 studies reporting data on 4,850 patients. We found that adenovirus (n = 44) is the most common OV in clinical trials with more than two-thirds (n = 108) using modified or recombinant viral backbones, and granulocyte-macrophage colony-stimulating factor (GM-CSF; n = 40) was the most common transgene. The most common tumors targeted were melanoma (n = 1,997) and gastrointestinal (GI; n = 916) cancers with the most common monotherapy received by intratumoral (n = 3,003) or intravenous (n = 1,318) delivery routes. The most common combination included chemotherapy (n = 54).Treatment-related adverse events included low-grade constitutional symptoms and local injection site reactions. Measurements of virus shedding were frequently performed, but many studies were limited to blood and tumor tissue analysis, using only polymerase chain reaction (PCR). Although most studies reported antiviral antibody titers (n = 101), only a few reported virus-specific T-cell responses (n = 23). Objective responses were recorded in 458 (9.4%) patients and disease control was achieved in 1,141 (23.5%) patients, although standard reporting criteria were used in only 60.4% of cases.These data provide an insight into the current state of clinical research on OVs and highlight potential areas requiring further investigation to better define the role of OVs in cancer treatment.